PKW Budidaya Sayuran Hidroponik di Desa Pekalongan Kecamatan Batealit Kabupaten Jepara - Syakhroni, Akhmad; M. Sagaf; Marlyana, Novi (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
One of the hydroponic vegetable cultivators in Jepara district, Mr. Ryan Arfian with his business named Bagus Hydrofarm (Mitra) has problems in the field of low production capacity. This is because partners only have 800 mature planting points. The production process of hydroponic vegetables is also still low because there is no quality control on the product. This problem arises because there is no partner's knowledge about the production process and quality control that is sufficient and good. there is no humidity and temperature measuring instrument. The results of the increased benefits from this regional partnership program are an increase in production capacity by 17.5%, an increase in knowledge of how to cultivate hydroponic vegetables by 100%, an increase in assets in the form of measuring instruments for PH and TDS by 100%, an increase in assets in the form of measuring devices for temperature and humidity by 100 %, increased knowledge about good business management by 100%.